2014
DOI: 10.2516/ogst/2013216
|View full text |Cite
|
Sign up to set email alerts
|

Control-Oriented Models for Real-Time Simulation of Automotive Transmission Systems

Abstract: -A control-oriented model of a Dual Clutch Transmission (DCT) was developed for realtime Hardware In the Loop (HIL) applications, to support model-based development of the DCT controller and to systematically test its performance. The model is an innovative attempt to reproduce the fast dynamics of the actuation system while maintaining a simulation step size large enough for real-time applications. The model comprehends a detailed physical description of hydraulic circuit, clutches, synchronizers and gears, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Sorniotti sprag clutch to the traditional MT, although it is difficult to shift seamlessly due to the MTs' layout [17]. Two clutches are used in a DCT for removing the torque interruption during gear-shifting [18,19]. Ruan et al [20] developed three case layouts of powertrain system for EVs, and they found that CVT can reduce energy consumption, and manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%
“…Sorniotti sprag clutch to the traditional MT, although it is difficult to shift seamlessly due to the MTs' layout [17]. Two clutches are used in a DCT for removing the torque interruption during gear-shifting [18,19]. Ruan et al [20] developed three case layouts of powertrain system for EVs, and they found that CVT can reduce energy consumption, and manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%